2010
DOI: 10.3748/wjg.v16.i5.554
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis D: Scenario in the Asia-Pacific region

Abstract: Hepatitis D virus (HDV) infection is present worldwide and affects all age groups. Around 18 million people are estimated to be infected with HDV. An important trend in HDV infection is global decline. HDV prevalence has decreased significantly in Europe since the 1970s and 1980s when it was first reported. The Asia-Pacific region now seems to be where HDV is a major health concern. There is a lack of available data from most of the countries from this region; hence, the true status of HDV cannot be determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 59 publications
2
88
0
Order By: Relevance
“…The prevalence of anti-HD was only 0.32% in a mixed-hospital HBsAg population collected in the country from 2008 to 2010 (Kim et al 2011). There has been no report of significant HDValso, in Japan, except for a high prevalence in the Mikayo Islands, Okinawa (Abbas et al 2010), where up to 23% of the HBsAg carriers were found to be infected with HDV in the 1990s; the prevalence of HDV in the area had decreased to 8.5% in 2000 (Arakawa et al 2000).…”
Section: Epidemiology Of Hdv At the Fingertips In The 1980s -1990smentioning
confidence: 99%
“…The prevalence of anti-HD was only 0.32% in a mixed-hospital HBsAg population collected in the country from 2008 to 2010 (Kim et al 2011). There has been no report of significant HDValso, in Japan, except for a high prevalence in the Mikayo Islands, Okinawa (Abbas et al 2010), where up to 23% of the HBsAg carriers were found to be infected with HDV in the 1990s; the prevalence of HDV in the area had decreased to 8.5% in 2000 (Arakawa et al 2000).…”
Section: Epidemiology Of Hdv At the Fingertips In The 1980s -1990smentioning
confidence: 99%
“…Forty-two (53.1%) of these 79 patients were inactive HBsAg carriers, while 34 (43.1%) of them had active chronic hepatitis B infection, two (2.5%) had liver cirrhosis and one (1.2%) of had hepatocellular cancer. [12,13]. Although the seroprevalence has decreased due to preventive measures and vaccination, it is still a problem.…”
Section: Resultsmentioning
confidence: 99%
“…In Japan, the prevalence of antibodies against HDV (anti-HDV) ranges from 21.3% to 63.3% in Okinawa: these high figures are due to older HBV carriers, and reflect previous acquirement of HDV infection in that cohort [23]. Taiwan was endemic for hepatitis B before vaccination [22]. From June 1983 to May 1995, similarly to the decline in HBV infection, the HDV prevalence in HBsAg carriers decreased considerably to 4.4% [24].…”
Section: Introductionmentioning
confidence: 98%
“…The prevalence rate of HDV infection in asymptomatic HBV carriers was reported as 2%, 31%, and 3.3% in Jordan, Kuwait, and Saudi Arabia, respectively [17][18][19]. In chronic liver diseases, it was reported as 23.5%, 23%, 2%, and 10% in Egypt, Jordan, Yemen, and Iran respectively [15,17,[20][21][22]. The prevalence of HDV infection was low (0.5% to 13.3%) in Japan except in some islands of Okinawa, Russia except in Yakutia (18-20%), Korea, Indonesia (< 0.05%), Malaysia, Thailand (0.7%), Philippines and Vietnam (1.3%), and Lebanon (1.2%) [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation